2018
DOI: 10.3389/fpsyg.2018.00412
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Second Language (L2) Proficiency on Cognitive Control Among Young Adult Unbalanced Chinese-English Bilinguals

Abstract: The current study investigates the influence of L2 proficiency on cognitive control among three matched groups of unbalanced Chinese-English bilinguals. Flanker task was administered to measure conflict monitoring and inhibition, and Wisconsin Card Sorting Test (WCST) to measure mental set shifting. ANOVA analyses of the Flanker results showed no differences in inhibition across all groups and no interaction between group and condition. However, the Flanker results showed faster performance for the highest L2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 64 publications
3
32
0
Order By: Relevance
“…On the one hand, Yudes and colleagues [41] found that interpreters outperformed unbalanced-late bilinguals and monolinguals, which is what one would expect based on the bilingual advantage hypothesis. On the other hand, Xie [65] found no differences in scores between the high proficiency, the middle proficiency, and the low proficiency bilingual groups; similar results were found by Kousaie and colleagues [48], who also found no group differences between bilinguals and monolinguals. Van der Linden and colleagues [68], found no evidence in favor of a bilingual advantage on the N-back task and the Hebb repetition paradigm.…”
Section: Other Experimental Taskssupporting
confidence: 75%
See 2 more Smart Citations
“…On the one hand, Yudes and colleagues [41] found that interpreters outperformed unbalanced-late bilinguals and monolinguals, which is what one would expect based on the bilingual advantage hypothesis. On the other hand, Xie [65] found no differences in scores between the high proficiency, the middle proficiency, and the low proficiency bilingual groups; similar results were found by Kousaie and colleagues [48], who also found no group differences between bilinguals and monolinguals. Van der Linden and colleagues [68], found no evidence in favor of a bilingual advantage on the N-back task and the Hebb repetition paradigm.…”
Section: Other Experimental Taskssupporting
confidence: 75%
“…Of the 56, 46 were original studies [7,14,21,, and 10 were review/meta-analysis studies [70][71][72][73][74][75][76][77][78][79]. The bilingual studies were conducted on several continents, with 23 (41.1%) having been conducted in North America (particularly in Canada) [14, 21, 27, 29-32, 34, 38, 45, 48, 53-55, 60, 63, 69-72, 74, 75, 78], 5 (8.9%) having been conducted by a North American/European collaboration [36,42,47,50,58], 2 (3.6%) having been conducted by a North American/Asian collaboration [54,61], 1 (1.8%) having been conducted by a North American/European/Asian collaboration [28], 18 (32.1%) having been European studies [33, 35, 37, 39, 41, 43, 46, 49, 51, 52, 57, 64, 66-68, 73, 76, 77], 1 (1.8%) having been conducted by an European/Australian collaboration [40], 2 (3.6%) having been conducted by an European/Asian collaboration [7,79], and 4 (7.1%) having been Asian studies [44,59,61,65]. To date, of 28 African or Latin American studies on bilingualism and cognitive control still have not been published.…”
Section: General Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study by Xie (2018), it was shown that among the three bilingual groups varying in L2 proficiency, the high L2 proficiency bilingual group performed faster than the low L2 proficiency bilingual group in congruent, neutral, and incongruent trials, which further proves that bilingualism is significantly related to response times, which presumably reflects conflict monitoring. However, the regression analyses results of the current study showed no relation between bilingualism and mental set shifting.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, as a result of increased control demand, high-proficient bilinguals would develop a better ability to resolve conflict. At the same time, behavioral bilingualism studies have produced a number of inconsistent outcomes, even when deploying continuous measures of BEFs, with studies failing to firmly establish an effect of L2 proficiency on executive performance, either partially (i.e., in one of several executive tasks) or completely (e.g., Becker, Schubert, Strobach, Gallinat & Kühn, 2016;Dong & Xie, 2014;Rosselli, Ardila, Lalwani & Vélez-Uribe, 2016;Xie, 2018). Dong and Xie (2014), for instance, found no effect of varying L2 proficiency on the level of performance on the same Flanker task deployed in the present study.…”
Section: Effects Of Individual Differences In Befs On Executive Behavmentioning
confidence: 99%